Positive Solutions for a System of Semipositone Fractional Difference Boundary Value Problems. (18th July 2018) - Chen, Cheng; Xu, Jiafa; O'Regan, Donal; Fu, Zhengqing
Abstract : Using the fixed point index, we establish two existence theorems for positive solutions to a system of semipositone fractional difference boundary value problems. We adopt nonnegative concave functions and nonnegative matrices to characterize the coupling behavior of our nonlinear terms.